Insights into the synergistic effects of metal particles (Ag, Cu, and Fe) and urea on CO2 clathrate hydrate growth using molecular dynamics simulations - Sinehbaghizadeh, Saeed; Saptoro, Agus; Naeiji, P.; Tiong, Angnes Ngieng Tze; Mohammadi, A.H. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
A variety of industrial applications of hydrate-based CO2 capture and utilization technologies are hindered by the complex and slow hydrate formation; however, improving CO2 hydrate formation kinetics can be facilitated by adding the accelerators (promoters). In this regard, understanding the promotion mechanisms of these compounds on the hydrate formation at the molecular level would assist in either establishing feasible processes or finding more efficient promoters. In this work, CO2 hydrate growth and formation in the presence of hybrid metal particles (Ag, Cu, and Fe) and urea molecule has been explored through molecular dynamics (MD) simulation at below and above water freezing point. Different criteria were used to characterize and analyse the CO2 hydrate formation kinetics. The outcomes reveal that, although the mixture of Cu, Ag, and Fe metal particles has positive effects on the rate of hydrate formation above the ice point, the mixture of Cu, Fe, and urea (without the inclusion of Ag) in comparison with the other investigated systems, possesses the highest promotion effect on the clathrate hydrate growth rate. This combination of metal particles creates various functions in the solution phase adjacent to the hydrate surface. The metal particles and urea could promote the formation of new cages at the hydrate-solution boundary by decreasing the heat and mass transport resistances of CO2 in water. In addition, the improvement of combined metal particles and urea under water freezing was found to be less substantial. However, the behaviours of combined metal particles without urea at different thermodynamic conditions are quite dissimilar.